2021
DOI: 10.47405/mjssh.v6i5.777
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting PULSE 2 Textbook after Three Years: Have Teachers Changed Their Mind?

Abstract: The present study aims to further explore Malaysian secondary English teachers’ perspective on the use of PULSE 2 in their language classrooms, after three years of its introduction in Malaysian secondary schools. The study is qualitative in nature, employing semi-structured interview as the approach for data collection the data. However, due to the Movement Control Order (MCO) the study was conducted through a Mobile Instant Messaging (MIM) application, WhatsApp. ATLAS ti. was employed to perform the content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Meanwhile, the selection of the topics in the printed textbook should bear on public health, environmental concerns, and respect for all, and lessons drawn from COVID-19 itself and how they relate to their life in a greater sense (Chabbot & Sinclair, 2020). Not only that a printed textbook should also consider the local culture in its contents and topics, (Shak et al, 2021), to promote a sense of familiarity and relatedness among its potential users while lessening the anxiety of these users might experience in doing their remote learning individually. Even better, this printed textbook should strive to provide a balanced representation of foreign and local culture in its content, as suggested by (Deswila et al, 2021).…”
Section: Considerations In Producing Future Printed Textbooksmentioning
confidence: 99%
“…Meanwhile, the selection of the topics in the printed textbook should bear on public health, environmental concerns, and respect for all, and lessons drawn from COVID-19 itself and how they relate to their life in a greater sense (Chabbot & Sinclair, 2020). Not only that a printed textbook should also consider the local culture in its contents and topics, (Shak et al, 2021), to promote a sense of familiarity and relatedness among its potential users while lessening the anxiety of these users might experience in doing their remote learning individually. Even better, this printed textbook should strive to provide a balanced representation of foreign and local culture in its content, as suggested by (Deswila et al, 2021).…”
Section: Considerations In Producing Future Printed Textbooksmentioning
confidence: 99%
“…A few studies were conducted based on teachers' and students' perceptions of PULSE 2 in the secondary syllabus as they are the pertinent users of the current textbook. For instance, Shak et al (2021a); Johar and Azlina (2019) explored teachers' general perception of PULSE 2 in teaching and learning English in Malaysian schools. At the same time, Goh and Aziz (2020) attempted to explore the secondary school teachers' perception of the speaking activities in PULSE 2.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The bold decision to utilize foreign textbooks in Malaysian schools received mixed views from the stakeholders (Nazari & Aziz, 2020;Shak et al, 2021a). One concern is that the cultural content in the imported textbooks, PULSE 2 in the case of this study, is deemed as limited relevance to Malaysian students (Shak et al, 2021b).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Additionally, Goh and Aziz (2020) discovered that 46% of the surveyed English teachers who used PULSE 2 disagreed that the Speaking activities in the textbook use language that is at the right level of their pupils' current English ability. And more recently, Ya Shak et al (2021) reported that some teachers felt that the grammar level in PULSE 2 could be challenging and unsuitable for the learners unless the learners aspire to become an English teacher later. Likewise, some parts of the textbook were also believed to be too difficult, while the others were deemed as too easy.…”
Section: High Lexical Densitymentioning
confidence: 99%